Pengembangan Badan Usaha Milik Desa (BUMDes) Bantarsari Bogor: Peningkatan Penjualan Produk Melalui Marketplace - Ismail, Verni Yuliaty; Annisariza, Nelly Ulfah; Annisa, Intan Tri (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2024)
Bantarsari village located in Ranca Bungur subdistrict, Bogor regency, West Java, is part of Kategori Desa Maju (Developed Village Category) with an IDM score of 0,7525. One of the potential economic resilience that can be developed in Bantarsari village are village owned enterprises (BUMDes). The purpose of this community service is to boost sales and developed the potential of small businesses (UKM) that exists in Bantarsari BUMDes. The result of focus group discussion (FGD) by potential BUMDes and competency survey by UKM managers pertaining the solution to improve UKM, is to create a product sales workshop through marketplace. Participants of this activities are managers of UKM whose products will be sold through marketplace, managed by Bantarsari BUMDes. Participants are successfully registered to Shopee and are able to use the available feature by the application to promote and to increase the chances of their product being bought (check out) by potential buyer.